A Novel Method of Design of Miniaturized Microstrip Branch-Line Couplers - D. A. Letavin; Y. E. Mitelman; V. A. Chechetkin (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The design of miniature quadrature bridge devices based on replacement of a segment of microstrip transmission line on a low-pass filter, which has the same phase shift that model segment is described. The simulation of the proposed designs are held and their frequency characteristics are obtained. Prototypes and the results of measurement of their characteristics, confirming the efficiency of the device are presented.